The Influence of Leadership, Motivation, and Discipline on the Performance of Koni Office Employees in North Kalimantan Province - Muhammd Nasir; Sulastini Sulastini; Maskur Maskur (Cita Konsultindo Research Center, 2024)
Due to the current employee's background, many problems arise related to employment, especially employee performance, therefore problems related to performance need to find a solution. Employees have a very important role and they are the main driver of smooth performance. Therefore, attention to human resources, which is one of the factors for achieving organizational goals, is appropriate for Koni, North Kalimantan Province. This research focuses on three problems, namely (1) Is there a partial influence of leadership on employee performance, (2) Is there a partial influence of motivation on employee performance, (3) Is there a partial influence of work discipline on employee performance, and (4) Is there an influence of leadership, motivation, and discipline together on employee performance. This research method uses a quantitative approach. The number of samples taken was 48 respondents using a saturated sampling technique. The data collection technique uses a questionnaire (questionnaire), while data analysis uses multiple linear regression analysis using SPSS Version 23 software. The results of the research show that Leadership, Motivation, and Work Discipline have a significant effect on Employee Performance at the Koni Office of North Kalimantan Province, both partially and simultaneously Keywords: Leadership, Motivation, Work Discipline, Employee Performance